Phosphatidylethanol levels and their association with withdrawal severity among individuals with severe alcohol use disorder seeking inpatient withdrawal management - Lee, Jeong Hoo; Szpak, Veronica; Vercollone, Lisa W.; Chai, Peter R.; Goldfine, Charlotte E.; Maddams, Samuel; Suzuki, Joji (Frontiers in Psychiatry, 2025)
IntroductionThis study aimed to determine if phosphatidylethanol (PEth) levels are associated with alcohol withdrawal severity among individuals seeking inpatient withdrawal management.MethodsA prospective study enrolled individuals undergoing alcohol withdrawal treatment at a ASAM level 4 inpatient unit. Primary outcome was the association between serum PEth levels with alcohol withdrawal medication requirements in diazepam equivalent (mg). Secondary objectives examined associations between PEth levels, Clinical Institute Withdrawal Assessment for Alcohol (CIWA) scores, drinking history, Alcohol Use Disorders Identification Test (AUDIT), and Prediction of Alcohol Withdrawal Severity Scale (PAWSS) scores.ResultsThirty participants (mean age 48.7 years, SD 11.7; 67.7% white) reported average daily alcohol consumption of 14.2 drinks (SD 11.4, range 1.2-47.6) and percent heavy drinking days of 72% (SD 31.9, range 13.3-100). Nine (29%) reported history of withdrawal seizures and seven (22.6%) reported history of delirium tremens. Admission PEth (PO, ng/mL) levels (mean 934.9, SD 546.6; range 42 - 2000-) did not significantly associate with total medication requirements (r=0.05, p=0.78) or CIWA scores (r=0.09 to -0.14, p>0.05). PEth levels showed no significant correlations with AUDIT (r=0.17, p=0.35) or PAWSS scores (r=0.13, p=0.50). However, significant correlations were found between PEth levels and average drinks per day (r=0.54, p=0.002), as well as with the percentage of heavy drinking days (r=0.54, p=0.002).Discussion and conclusionsConsistent with prior reports, PEth levels appear to correlate with patients’ alcohol consumption including heavy drinking, but our results did not find that PEth levels predict alcohol withdrawal severity among heavy drinkers seeking inpatient withdrawal management. Further research is warranted to better understand the utility of PEth testing.